1998
DOI: 10.1002/(sici)1099-1212(199807/08)8:4<252::aid-oa425>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic bowing deformities in tubular bones

Abstract: Is bowing in long bones from an archaeological context representative of postmortem damage or genuine antemortem pathology? Bowing deformities (also known as traumatic bowing deformities, plastic bowing deformities, plastic bowing fractures and acute bowing fractures in the clinical literature) are true pathological entities that have only recently been recognized by clinicians. Bowing in long bones results from a force that exceeds the elastic properties of a given bone, producing a new plastic (bowing) respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…Traumatic bowing deformities, such as acute plastic bowing deformities (APBD), in which deformation occurs without complete fracture, may also cause deformation of long bones. In a review of the subject by Stuart-Macadam et al (1998), it was found that most cases of APBD occurred in children and that the forearm was the most frequently affected site. The condition is rare and deformities may be resolved during normal growth and development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traumatic bowing deformities, such as acute plastic bowing deformities (APBD), in which deformation occurs without complete fracture, may also cause deformation of long bones. In a review of the subject by Stuart-Macadam et al (1998), it was found that most cases of APBD occurred in children and that the forearm was the most frequently affected site. The condition is rare and deformities may be resolved during normal growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…The condition is rare and deformities may be resolved during normal growth and development. The study by Stuart-Macadam et al (1998) found that a very small number of cases of APBD occurred in adults, where the fibula was the most frequently affected bone. In adults, industrial accidents were the most common cause.…”
Section: Discussionmentioning
confidence: 99%
“…In the broadest sense, bowing resulting from mechanical forces is due to trauma, i.e., a trauma to a degree lower than breaking stress (Angle, 1954; Swischuk and John, 1995; Stuart‐Macadam et al, 1998), which brings in another possible etiology.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Stress ranging between elastic and fracture limits causes bending that remains after stress is removed. Lower arm bones are the bones most frequently involved, typically a result from a fall onto an outstretched hand (Naga and Broadrick, 1977;Stuart-MacAdam et al, 1998). In many instances, the fracture of one of the lower arm bones is associated with APBD of the other bone (Borden, 1975;Crowe and Swischuck, 1977;Resnick et al, 1995;Price, 1996).…”
Section: Towards a Diagnosismentioning
confidence: 99%